TIIE-28 swaps as risk-adjusted forecasts of monetary policy in Mexico - Santiago García-Verdú; Manuel Ramos-Francia; Manuel Sánchez-Martínez (Banco de México, 2018)
Information extracted from financial derivatives on interest rates is commonly used to forecast movements in such rates. Yet, such an extraction generally assumes that agents are risk-neutral. Thus, it might be useful to account for their risk-aversion when doing forecasts. This can be done adding a risk-correction. In this context, we use TIIE-28 swaps to forecast changes in monetary policy in Mexico, using financial variables to account for the risk-correction. We assess whether models with a risk-correction outperform the TIIE-28 swaps rates. Their in-sample explained variability improves when using a risk-correction. Our main model's out-of-sample forecasts are similar for short horizons (3-month), and statistically better for longer horizons (9 to 24-month), compared to the direct use of TIIE-28 swaps interest rates.
Keywords: E52; G12; 330; TIIE-28; Swaps; Interest Rates; Expected Monetary Policy